2013
DOI: 10.1074/jbc.m112.432104
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-322 (miR-322) and Its Target Protein Tob2 Modulate Osterix (Osx) mRNA Stability

Abstract: Background: miRNAs exert important roles during osteoblast proliferation and differentiation. Results: miR-322 induces expression of osteogenic genes by down-regulation of expression of Tob2, which binds to the 3Ј-UTR of Osx and modulates its degradation. Conclusion: miR-322 and its target Tob2 are regulators of osteogenesis through control of Osx mRNA degradation. Significance: We have identified a miRNA-transcription factor network that allows fine-tuning of the osteoblast differentiation program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 55 publications
3
57
0
Order By: Relevance
“…For instance, Li et al (2008) conducted a miRNA screening during BMP2-induced osteogenesis in C2C12 cells and found that the expression of almost all miRNAs was downregulated during osteoblast differentiation. These data have been confirmed by other groups (Gamez et al 2013). The same authors also described miR-133 and miR-135 as negative regulators of osteogenesis that act by directly targeting Runx2 and Smad5 respectively, thereby inhibiting osteogenic differentiation (Li et al 2008).…”
Section: The Interplay Between Mirnas and Bmp Signalingsupporting
confidence: 75%
See 3 more Smart Citations
“…For instance, Li et al (2008) conducted a miRNA screening during BMP2-induced osteogenesis in C2C12 cells and found that the expression of almost all miRNAs was downregulated during osteoblast differentiation. These data have been confirmed by other groups (Gamez et al 2013). The same authors also described miR-133 and miR-135 as negative regulators of osteogenesis that act by directly targeting Runx2 and Smad5 respectively, thereby inhibiting osteogenic differentiation (Li et al 2008).…”
Section: The Interplay Between Mirnas and Bmp Signalingsupporting
confidence: 75%
“…downregulated, thus avoiding Dlx5 and Osx miRNArelated repression (Itoh et al 2009). The expression of miR-322 is also downregulated by BMP2 and has been shown to indirectly repress Osx expression to facilitate further osteogenic differentiation (Gamez et al 2013).…”
Section: The Interplay Between Mirnas and Bmp Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNA microarray profiling was carried out using the Agilent platform (Genotypic Technology Private Ltd.). Quantitative PCRs were performed using the StepOne real-time PCR system and a TaqMan 5Ј nuclease probe method (Applied Biosystems) (miRNA transcripts normalized to U6) (13)(14)(15).…”
Section: Methodsmentioning
confidence: 99%